2001
DOI: 10.1046/j.1365-2168.2001.01618.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopically assisted total or distal gastrectomy with lymph node dissection for early gastric cancer

Abstract: A technique of laparoscopic gastrectomy with lymph node dissection for early invasive gastric cancer is described. A definitive answer concerning the appropriate level of lymph node dissection and the role of laparoscopic gastrectomy in the treatment of more advanced gastric cancer remains to be defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 10 publications
2
78
1
2
Order By: Relevance
“…From an oncological point of view, curative resections with similar survival rates have been obtained in early gastric cancer (EGC) cases [7][8][9][10][11]. However, long-term results in more advanced cases are not still available.…”
Section: Introductionmentioning
confidence: 99%
“…From an oncological point of view, curative resections with similar survival rates have been obtained in early gastric cancer (EGC) cases [7][8][9][10][11]. However, long-term results in more advanced cases are not still available.…”
Section: Introductionmentioning
confidence: 99%
“…In 1994 Kitano et al [1] reported the first laparoscopic gastric resection and Billroth reconstruction in a patient with early gastric cancer (EGC). Laparoscopic gastric surgery (LGS) has been shown to improve short-term results and quality of life, compared to standard techniques [2,3,4] and has become an acceptable alternative approach in the management of EGC especially in Japan and Korea [5,6,7] . The experience of laparoscopic gastric surgery in the western world is smaller because most of the gastric cancers are seen in an advanced stage and LGS is not considered an acceptable alternative to standard open surgery as yet.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to say that methods for reconstruction after resection have reached a level similar to laparotomy. Complications of LADG, including hemorrhage, intraperitoneal abscess, pancreatic fistula, ileus, respiratory complications, and wound infection, account for up to 1%, whereas complications regarding reconstruction for ruptured sutures and stenosis of the anastomotic part, etc., account for 1 to 6% [7][8][9][10][11][12]. This indicates the difficulty of performing anastomosis in laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%